2013
DOI: 10.1093/ntr/ntt093
|View full text |Cite
|
Sign up to set email alerts
|

Development and Preliminary Randomized Controlled Trial of a Distress Tolerance Treatment for Smokers With a History of Early Lapse

Abstract: Reasons for the decrease in abstinence in DT after treatment discontinuation and suggestions for future research are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
54
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 41 publications
(48 reference statements)
7
54
2
Order By: Relevance
“…Extant evidence supports the efficacy of behavioral treatments that target reducing EA to facilitate smoking cessation (Bricker, Wyszynski, Comstock, & Heffner, 2013; Brown, et al, 2013; Gifford, et al, 2004; Gifford, et al, 2011; Hernandez-Lopez, Luciano, Bricker, Roales-Nieto, & Montesinos, 2009). In particular, Gifford et al (2004; 2011) demonstrated that cessation success was mediated by reduction in a self-reported measure of smoking-specific EA (i.e., tendency to smoke in order to reduce or avoid the specific physical, cognitive, and affective distress associated with nicotine withdrawal and craving).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Extant evidence supports the efficacy of behavioral treatments that target reducing EA to facilitate smoking cessation (Bricker, Wyszynski, Comstock, & Heffner, 2013; Brown, et al, 2013; Gifford, et al, 2004; Gifford, et al, 2011; Hernandez-Lopez, Luciano, Bricker, Roales-Nieto, & Montesinos, 2009). In particular, Gifford et al (2004; 2011) demonstrated that cessation success was mediated by reduction in a self-reported measure of smoking-specific EA (i.e., tendency to smoke in order to reduce or avoid the specific physical, cognitive, and affective distress associated with nicotine withdrawal and craving).…”
mentioning
confidence: 94%
“…Distress tolerance and experiential avoidance are related but distinct constructs, with experiential avoidance serving as a strategy or function used by individuals low in distress tolerance (Boulanger, Hayes, & Pistorello, 2010). A recent innovation in behavioral smoking cessation treatment has been a shift in focus from reduction of distress severity to reduction of smokers’ EA (Hayes, et al, 1996), and their reactivity to such distress (Brown et al, 2008; Brown et al, 2013; Gifford et al, 2004; Gifford et al, 2011). Beyond smoking, EA has been found to be a central construct in changing mental and behavioral health problems (e.g., Hayes, Luoma, Bond, Masuda, & Lillis, 2006; Hayes, Masuda, Bissett, Luoma, & Guerrero, 2004).…”
mentioning
confidence: 99%
“…Although DI is relatively stable and trait-like (e.g., Cummings et al, 2013), it is also hypothesized to be modifiable with intervention. Indeed, treatments targeting DI have been associated with positive outcomes for substance use disorders (Bornovalova, Gratz, Daughters, Hunt, & Lejuez, 2012; Brown et al, in press). Reduction of DI in treatment may both (1) enhance behavioral and functional outcomes by improving the ability to persist toward goals in the context of distress, and (2) reduce maladaptive avoidance behaviors motivated by DI.…”
mentioning
confidence: 99%
“…A recent study found that a DI-targeted treatment for smoking cessation impacted hypothesized mediators (e.g., experiential avoidance), providing some support that the treatment successfully reduced DI (Brown et al, in press). In addition, a pilot study of a DI treatment for substance use disorders found significant reductions in behavioral measures of DI over time (Bornovalova et al, 2012).…”
mentioning
confidence: 99%
“…As mental and physical health is intertwined, interventions to promote smoking cessation deserve to be fully integrated within health care delivery systems [1]. Furthermore, techniques used in mental health care such as distress tolerance skills or working upon cognitive distortions might present combined benefits for smoking cessation too [40,41].…”
Section: Discussionmentioning
confidence: 99%